In Metastatic Non-small cell Lung Cancer Platinum-Based Treated Patients, Herbal Treatment Improves the Quality of Life. A Prospective Randomized Controlled Clinical Trial - Guo, Huiru; Liu, Jia X.; Li, Hegen; Baak, Jan P. A. (Frontiers in Pharmacology, 2017)
Background According to clinical experience, Traditional Chinese Medicine (TCM) herbs added to platinum-based therapy (PBT) improve the Quality of Life (QOL) in metastatic Non-Small Cell Lung Cancer (NSCLC) patients, but this must be prospectively validated. Patients and Methods Based on clinical impressions regarding the effect of adding TCM herbs to platinum-based chemotherapy, we anticipated that 2 x 21 patients would be sufficient to obtain significant results with an α<0.05 and power (1-β) of 90%. To be on the safe side, we enrolled at least 28 patients in each group. In a prospective randomized controlled trial, sixty-one uniquely defined consecutive patients (PBT+PLACEBO, N=32; PBT+TCM, N=29) with stage IIIB-IV, Eastern Cooperative Oncology Group (ECOG) performance scores=PS 0-1 and TCM syndrome combined Qi-Yin deficiency were enrolled. These 61 patients were selected from originally 154 consecutive stage IIIB-IV lung cancer patients in the enrollment period. Patients were hospitalized and strictly controlled/surveyed during the entire 2-month treatment period, to guarantee use of or abstinence from TCM herbal and placebo fluids. Occurrence of nausea-vomiting, QOL by Functional Assessment of Cancer Therapy-Lung (FACT-L) scales and changes in Eastern Cooperative Oncology Group (ECOG) “improved and stable rates” were compared before and after two treatment cycles. Results Before treatment, the clinico-pathologic and QOL features in PBT+PLACEBO and PBT+TCM patients did not differ (P＞0.10). The only side effects attributed by some of the patients to the TCM herbs were transient, mild gastric/abdominal heaviness in the first 2 weeks, but these also occurred amongst the PBT+PLACEBO patients (17% and 13%, P>0.10). The incidence rates of nausea during treatment were 17% in PBT+TCM versus 75% in PBT+PLACEBO; vomiting rates were 14% and 56% (P<0.0001; 0.002). Moreover, ECOG “improved and stable rates” were 90％ in the PBT+TCM versus 69% in the PBT+PLACEBO group (P=0.04). In PBT+TCM patients, FACT-L social/familial and functional subscales were better after 2 months’ treatment (P=0.02, 0.03). Contrarily, in PBT+PLACEBO patients, the QOL variables total score, physical and emotional subscales were worse after PBT treatment (P=0.03, 0.0001, 0.003). Conclusions In stage IIIB-IV ECOG-PS=0-1 NSCLC patients with Qi-Yin deficiency and platinum-based chemotherapy, adding TCM herbal medication improves the QOL.